Identification and expression analysis of NAC transcription factors potentially involved in leaf and petal senescence in Petunia hybrida - Trupkin, Santiago Ariel (2019)
Progression of leaf senescence depends on several families of transcription factors. In Arabidopsis, the NAC family plays crucial roles in the modulation of leaf senescence; however, the mechanisms involved in this NAC-mediated regulation have not been extensively explored in agronomic species. Petunia hybrida is an ornamental plant that is commonly found worldwide. Decreasing the rate of leaf and petal senescence in P. hybrida is essential for maintaining plant quality. In this study, we examined the NAC-mediated networks involved in regulating senescence in this species. From 41 NAC genes, the expression of which changed in Arabidopsis during leaf senescence, we identified 29 putative orthologs in P. hybrida. Analysis using quantitative real-time-PCR indicated that 24 genes in P. hybrida changed their transcript levels during natural leaf senescence. Leaf-expressed genes were subsequently assessed in petals undergoing natural and pollination-induced senescence. Expression data and phylogenetic analysis were used to generate a list of 10–15 candidate genes; 7 of these were considered key regulatory candidates in senescence because of their consistent upregulation in the three senescence processes examined. Altogether, we identified common and distinct patterns of gene expression at different stages of leaf and petal development and during progression of senescence. The results obtained in this study will contribute to the understanding of NAC-mediated regulatory networks in petunia.